Bank of Baroda - Asrani, Tanisha (ATLAS SkillTech University, 2025)
The global banking industry is critical to the economy's stability and smooth operation since it regulates the movement of money and serves as a financial reservoir for consumers and corporations alike. Banks help economies function by providing vital services like loans, investment possibilities, and financial risk management via a structured and organized network. This sector is often overseen by extensive government laws, which frequently involve both federal and state agencies, and is supported by a variety of financial institutions that supervise monetary flow and risk management. Over the years, the banking industry has expanded its reach, serving a vast and diverse customer base and creating millions of job opportunities worldwide. Despite this growth, pinpointing the exact number of employees within the banking sector remains challenging due to its extensive and varied nature. The industry's global assets are valued in the trillions of dollars, reflecting its immense scale and significance. The banking industry is broadly categorized into several sectors, including investment banking, retail banking, cooperative banking, and rural banking, all of which fall under the larger umbrella of the global banking system.
Project Report on Bank of Baroda (2023-2025) Under the Guidance of Prof. Vaibhav Shukla
Keywords: global banking industry